Job Satisfaction, Motivation and Performance at Self-Managing Teams - Avdiaj, Besnik; Ziberi, Besime (FEB - Universitas Lampung, 2019)
Self-managing teams have occupied the modern organizations. Even though it is still in its commencement, the theory of self-managing teams is developing with fulminant steps towards imposing this philosophy to most of the organizations operating in dynamic environments. Thus, studying these semi-autonomous or entirely independent formations is particularly important in order to follow the global trends of management. In this spirit, this study discusses some human aspects which are influenced by self-managing philosophy, respectively it analyses the relationships between team self-management and job satisfaction, motivation and perceived performance. This is supported theoretically by a bunch of studies which discuss predictive elements for creation of self-managing teams, the outcomes as a result of team self-management and others that discuss both inputs and outcomes. Respondents were surveyed through self-reporting questionnaire, comprising of several instruments tested in previous studies. 55 respondents of 19 entrepreneurial start-up teams have been surveyed. According to the results calculated through SPSS, it is confirmed that team self-management is positively related to job satisfaction and perceived performance of team members. However, from regression and correlation analysis, it appears that there is no stable relationship between team self-management and motivation.